2021
DOI: 10.1093/tbm/ibab103
|View full text |Cite
|
Sign up to set email alerts
|

Pivoting during a pandemic: lessons learned from transitioning a multisite randomized controlled trial to a remote protocol in response to COVID-19

Abstract: THR1VE! is an ongoing multisite randomized clinical trial of a positive psychology intervention designed to treat diabetes distress and improve glycemic outcomes in teens with type 1 diabetes. Due to the COVID-19 pandemic restrictions on clinical research and changes in diabetes clinical care, THR1VE! was adapted from an in-person enrollment protocol to a remote protocol through a series of development and testing strategies. We discuss the process of transitioning the protocol and the demonstrated feasibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…First, large-scale, fully remote data collection started close to the declaration of the COVID-19 pandemic in the United States, which is known to have changed our behavior and interaction with technology and devices [ 74 ]. Indeed, Inverso et al [ 75 ] showed higher engagement rates during the COVID-19 pandemic because of an increased reliance on technology during the lockdown. The WASH study began recruitment on March 15, 2020, shortly after the World Health Organization declared COVID-19 a pandemic on March 11, 2020.…”
Section: Discussionmentioning
confidence: 99%
“…First, large-scale, fully remote data collection started close to the declaration of the COVID-19 pandemic in the United States, which is known to have changed our behavior and interaction with technology and devices [ 74 ]. Indeed, Inverso et al [ 75 ] showed higher engagement rates during the COVID-19 pandemic because of an increased reliance on technology during the lockdown. The WASH study began recruitment on March 15, 2020, shortly after the World Health Organization declared COVID-19 a pandemic on March 11, 2020.…”
Section: Discussionmentioning
confidence: 99%
“…That said, to date baseline and follow-up surveys are completed by participants 87% of the time on average, which is equivalent or better than anticipated for a fully remote trial. 4 , 43 45 Second, it is unclear the degree to which using the Bluetooth scale for weight measurements will impact our outcomes, because regular weighing may improve weight loss or weight loss maintenance. 39 We will need to consider this in our post hoc analyses.…”
Section: Discussionmentioning
confidence: 99%
“… 1 3 Most behavioral health intervention trials in the U.S. have had to pivot to fully remote intervention and evaluation protocols as a result of restrictions on in-person research activities. 4 6 Moving these trials into a fully remote format, however, was not without precedence. Prior to the COVID-19 pandemic, research had shown the promise and challenges with these pivots across all stages of research, including participant recruitment, intervention delivery, and data collection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other ongoing behavioral interventions [ 82 ], research focused on young children and T1D has adapted over the last few years to accommodate reliance on telehealth diabetes visits [ 83 ]. The necessity for remote delivery of interventions across this time period may prove advantageous for the future of intervention delivery, maximizing family convenience and reducing barriers that are commonly reported regarding participation in research [ 84 , 85 ].…”
Section: Current Issuesmentioning
confidence: 99%